2021
DOI: 10.4103/jmh.jmh_23_21
|View full text |Cite
|
Sign up to set email alerts
|

Acute Presentation of Port Site Hernia Following Robot-Assisted Hysterectomy

Abstract: Port site hernia (PSH) has been reported following both laparoscopic and robotic surgery. Subsequent surgical intervention increases postoperative morbidity. We report the case of a PSH through the 8-mm trocar following robot-assisted hysterectomy in a 49-year-old female patient, along with a review of the literature. The case was performed with the standard protocol; however, increased intraoperative bleeding was encountered from right uterine artery and vein. Discharged at 48 h, she presented in emergency on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…86.6% had less than 24 hours of LOS and 13.4% patients stayed more than 24 hours but none beyond 72 hours. We had one case of readmission who presented as a port site hernia after RH and needed exploration with end-to-end anastomosis [6]. There was no urinary tract injury in this series.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…86.6% had less than 24 hours of LOS and 13.4% patients stayed more than 24 hours but none beyond 72 hours. We had one case of readmission who presented as a port site hernia after RH and needed exploration with end-to-end anastomosis [6]. There was no urinary tract injury in this series.…”
Section: Resultsmentioning
confidence: 74%
“…They did not report any case of intra-operative hemorrhage, nerve injury, foreign bodies left in the peritoneal cavity, mechanical failure, or medical accidents. We did have one readmission for port site hernia on day 4 post operative day [6].…”
Section: Discussionmentioning
confidence: 97%
“…Sinha et al reported a case of acute TSH from the 8-mm trocar site following robotic hysterectomy and they suspected that the drain placement in the same port was one of the contributing factors. 13 They reviewed the literature, identifying 10 case reports of 8-mm TSH: nine of these with acute presentation, of which three following gynaecologic procedures, [14][15][16] five after urological surgery [17][18][19][20][21] and one after cholecystectomy 22 ; one case of 8mm TSH occurred 32 months after a lower anterior resection for rectal cancer. 23 TSH represents an uncommon complication following minimally invasive surgery, whose incidence varies from 0.1% to 2%.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, using the same instruments to perform multiple functions, such as using pro grasp forceps for both retraction and needle holders, reduces consumables costs. The overall minor complications such as port site discomfort/pain and minimal bleeding during surgery were <2%, and major complications such as port site hernia, bowel injury/bowel ischemia/gangrene, or massive bleeding due to vessel injury were <1% [ 26 ]. Acceptable low morbidity and complications were seen in the current study and have been similarly reported in the literature [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%